PENGARUH pH DAN KARAKTERISTIK AIR PADA PEMBENTUKAN LOW MOLECULAR WEIGHT ORGANIC: ALDEHIDA, AKIBAT PROSES PRADESINFEKSI DENGAN OZON - Mohammad Rangga Sururi (Purifikasi, 2009)
The aim of this research was to determine the influence of pH and water characteristics to low molecular weight (LMW) organic formation, particularly aldehydes, in predisinfection process by using ozone. Ozone gas can be supplied continually into batch system contactors of 7 L volume. The measurement was done at contact time of 3, 5, and 10 minutes at any pH conditions. The water sample was taken from WTP of Water Supply Company of Bandung City. Based on the research, aldehyde composition percentage which was detected by GC-MS, had increased gradually until a contact time of 10 minutes. This result was influenced by the quantity of hydrophobic nature of organic matter in water sample. At residual concentration of ozone/TOC below 0,012, aldehyde was not detected either at acidic or basic pH, but was detected at neutral condition at any range of contact time. Aldehyde formation was influenced by the quantity and kinds of precursors, their concentrations and contact time of ozonation. In addition, pH value gave significant influence at the third minute of contact time.